6q deletion detected by fluorescence in situ hybridization using bacterial artificial chromosome in chronic lymphocytic leukemia. (24th May 2013) - Dalsass, Alessia; Mestichelli, Francesca; Ruggieri, Miriana; Gaspari, Paola; Pezzoni, Valerio; Vagnoni, Davide; Angelini, Mario; Angelini, Stefano; Bigazzi, Catia; Falcioni, Sadia; Troiani, Emanuela; Alesiani, Francesco; et al.
Abstract Deletions of the long arm of chromosome 6 are known to occur at relatively low frequency (3–6%) in chronic lymphocytic leukemia (CLL), and they are more frequently observed in 6q21. Few data have been reported regarding other bands on 6q involved by cytogenetic alterations in CLL. The cytogenetic study was performed in nuclei and metaphases obtained after stimulation with a combination of CpG‐oligonucleotide DSP30 and interleukin‐2. Four bacterial artificial chromosome (BAC) clones mapping regions in bands 6q16, 6q23, 6q25, 6q27 were used as probes for fluorescence in situ hybridization in 107 CLL cases in order to analyze the occurrence and localization of 6q aberrations. We identified 11 cases (10.2%) with 6q deletion of 107 patients studied with CLL. The trends of survival curves and the treatment‐free intervals (TFI) of patients with deletion suggest a better outcome than the other cytogenetic risk groups. We observed two subgroups with 6q deletion as the sole anomaly: two cases with 6q16 deletion, and three cases with 6q25.2–27 deletion. There were differences of age, stage, and TFI between both subgroups. By using BAC probes, we observed that 6q deletion has a higher frequency in CLL and is linked with a good prognosis. In addition, it was observed that the deletion in 6q16 appears to be the most frequent and, if present as the only abnormality, it could be associated with a most widespread disease.